Profil Penggunaan Antibiotik pada Pasien Klinik Anak di Rumah Sakit MM Indramayu Periode Januari-Maret 2021 - Siti Masripah; Meiti Rosmiati (Jurnal Health Sains, 2021)
Drugs are substances or combinations of substances, including biological products, which are used to influence or investigate physiological systems. Antibiotics are chemical substances produced by microorganisms that have the ability in aqueous solutions to inhibit the growth or kill microorganisms. This study uses non-experimental methods. The data collection was carried out retrospectively and presented in the form of a table. In this study, in the form of prescriptions for outpatient pediatric patients who used antibiotics at the MM Indramayu Hospital in the period January to March 2021, totaling 257 prescriptions. Based on data taken from outpatient pediatric patient prescriptions based on inclusion criteria. Patient criteria are patients who use antibiotics aged 0-11 years. The criteria for antibiotics included in the study were Rifampicin, Isoniazid, Pyrazinamide, Metronidazole, Cefadroxil, Cotrimoxazol, Cefixim. The strength of the antibiotics used are 100mg-450mg, 226mg, 70mg-300mg, 200mg-500mg, 30 mg, 100 mg, 125mg, 250mg, 500mg, 240mg, 125mg. The rules for using antibiotics are 1 x 1 powder, 2 x 1 ml, 2 x 1 cth, 2 x 1 tablet, 3 x 1 cth, 3 x 1 tablet. The dosage form of antibiotics used is powder, syrup and tablets. The results obtained include: the use of the most types of antibiotics, which is Rifampicin and Isoniazid antibiotics as many as 88 prescriptions (34.24%), the highest dosage strength is indicated by the use of Isoniazid strength 70mg-150 mg as many as 57 prescriptions (22.17%), the use of based on the rules of use, namely once a day, one dosage of pulveres rifampicin 450 mg by 88 prescriptions (34.24%), and the most antibiotic dosage forms used were pulveres/puyer preparations with 206 prescriptions (80.15%)